MEDIA EFFECTIVENESS OF ANDROID-BASED E-GEA APPLICATION TO IMPROVE CRITICAL THINKING SKILLS - Clara Adhi Pratiwi Sukmana Dewi; Chatarina Muryani; Sarwono Sarwono; Rita Noviani (Universitas Sebelas Maret (UNS), 2025)
This study aims to test the effectiveness of Android-based E-GeA learning media in improving the critical thinking skills of grade X students of SMA Negeri Kebakkramat, Karanganyar. The E-GeA application for Electronic Geography Adventure is designed to support geography learning through interactive features, such as learning videos, materials, animations, and pre-test and posttest-based exams. The study used an experimental and purposive sampling technique on 36 students in grades X-5. The data were analyzed using normality, n-gain, and t-test tests. The results showed that the t-test results showed a significant difference between the pre-test 30 and post-test 86 scores, with 94% of students achieving KKM scores. This study proves that E-GeA learning media improves students' critical thinking skills. These findings provide recommendations for integrating technology in geography learning to support improving the quality of education and skills in the 21st century.